2009
DOI: 10.1016/s1053-8119(09)70103-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered Cortico-Striatal Functional Connectivity in Obsessive-Compulsive Disorder

Abstract: Neurobiological models of obsessive-compulsive disorder (OCD) emphasize disturbances in the function and connectivity of brain corticostriatal networks, or "loops." Although neuroimaging studies of patients have supported this network model of OCD, very few have applied measurements that are sensitive to brain connectivity features. Objective: Using resting-state functional magnetic resonance imaging, we tested the hypothesis that OCD is associated with disturbances in the functional connectivity of primarily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2010
2010
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…In conclusion, previous research has established that the frontobasal brain region in OCD patients is metabolically hyperactive, functionally hyperconnected, and anatomically anomalous showing a combination of both regional volume expansions and reductions [Harrison et al, 2009;Menzies et al, 2008a;Pujol et al, 2004;Rotge et al, 2009]. In our study we identified subtle shape alteration in this part of the brain that may reflect disturbances during late brain development at ages when young people are particularly vulnerable to developing psychiatric illness.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…In conclusion, previous research has established that the frontobasal brain region in OCD patients is metabolically hyperactive, functionally hyperconnected, and anatomically anomalous showing a combination of both regional volume expansions and reductions [Harrison et al, 2009;Menzies et al, 2008a;Pujol et al, 2004;Rotge et al, 2009]. In our study we identified subtle shape alteration in this part of the brain that may reflect disturbances during late brain development at ages when young people are particularly vulnerable to developing psychiatric illness.…”
Section: Discussionsupporting
confidence: 55%
“…Functional imaging studies have indeed revealed abnormal activity and altered metabolism in frontostriatal circuits [Harrison et al, 2009;Menzies et al, 2008a;Pujol et al, 1999;Yü cel et al, 2007]. The alteration is also expressed in the anatomy, with regional volume increases and decreases that may vary during the course of the disorder [Marsh et al, 2009;Pujol et al, 2004;Rotge et al, 2009].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuropsychological deficits may play a mediating role between brain dysfunctions and clinical symptomatology ( Savage, 1998 ; Olley, Malhi, & Sachdev, 2007 ; Chamberlain et al, 2008 ; Harrison et al, 2009 ). Results of several studies indicated no significant correlation between the severity of OC symptoms and performance in neuropsychological test ( Bedard, Joyal, Godbout, & Chantal, 2009 ; Bucci et al, 2007 ); whereas some other researchers reported a significant correlation between them ( Abramovitch et al, 2011 ; Nedeljkovic et al, 2009 ; Segalas et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%